Persistent bifrontal rhinogenic contact headache - Santosh Kumar Swain; Debasmita Dubey (Journal of Clinical and Scientific Research)
Headache and facial pain may occur by the pressure of two opposing mucosal linings of the nasal cavity even in the absence of inflammatory disease. Anatomical variations such as deviated nasal septum (DNS), spur, concha bullosa, hypertrophied inferior turbinate, medialised middle turbinate and septal bullosa are important causes for contact headaches. DNS and spur are commonly found anatomical variations that result in rhinogenic contact headaches. However, S-shaped DNS causing persistent bifrontal headaches is rarely found in clinical practice. Diagnostic nasal endoscopy and computed tomography scans are important tools for the diagnosis of anatomical variations in the nasal cavity causing contact point headaches. Endoscopic resection of the contact point in the nasal cavity is the treatment of choice. We report the case of a 35-year-old woman presenting with a persisting bifrontal headache due to S-shaped DNS contacting with nasal mucosa. This unusual anatomical abnormality was treated by endoscopically assisted resection of the bilateral contact point and the patient was relieved from bifrontal headache.